On the Physical Significance of the Helmholtz Theorem in a Static Electromagnetic Field - Patrinos, Konstantinos (European Journal of Applied Sciences, 2023)
The study of the static electromagnetic field based on Maxwell’s equations and the Helmholtz theorem provides the possibility of understanding the physical reality regarding the phenomena that take place in the examined space of a moving, relative to the laboratory, source of an electrostatic field. Based on this study, the Biot-Savart law is derived and the importance of the generalized electromagnetic equations derived from the theory of the absolute system of reference is demonstrated. An in-depth examination of the structure of the electromagnetic field around a moving uniform linear distribution of charged elementary particles reveals the Biot-Savart magnetic field generation process.